Análise dos programas de integridade no setor público brasileiro - Barreto, Rodrigo Tavares de Souza (2019)
This research aims to investigate the extent to which the integrity programs implemented in the Brazilian direct public administration are in line with good international compliance practices. The study is in the field of Public Management, more specifically in the area of management of government agencies - although it combines corporate governance fundamentals, incorporated into the public sector through the adoption of the post-managerial principles of New Public Governance. The present diagnosis is exploratory, based on the cross-sectional analysis of the data collected and the proposed indicators. The sample is composed of twelve programs of integrity of direct administration organs belonging to the three spheres of government of the federation, among these, seven linked to the federal administration, two to the state and three allocated to the municipal sphere. The data were collected from the analysis of a series of documents regarding the process of implementing good integrity practices in each of the sample bodies, such as manuals, guides, integrity plans, codes of ethics and conduct, reports of investigations and audits, ordinances, resolutions, edicts, contracts, etc. The indicators were developed based on the guidelines and good practices of compliance indicated by the international anticorruption regime and systematic review of literature on the subject. Academically, the study discusses the best practices of compliance and its application to public sector organizations, in addition to proposing indicators associated to the process of implementation of these. In general, the results show that the evaluated programs have an adherence degree of 69.44% to the best international practices of compliance. Nevertheless, some compliance guidelines have low effective application in integrity programs, such as due diligence, with 39.58% adherence, and internal investigations, with 41.67%. It is also verified that the municipal entities have the lowest degree of adherence to the indicators, with 52.78%. On the other hand, state programs total 79.17% adherence to good compliance practices.